A review on challenges in empowerment of post-menopausal women in preventing fragility fractures from a Malaysian perspective - Mohd Ariff, Sharifudin; Nik Noor Kaussar, Nik Mohd Hatta; Mohd Said, Nurumal; Muhammad Lokman, Md. Isa; Azlina, Daud; Muhammad, Ibrahim; Samsul, Deraman (2020)
The incidence of osteoporosis is continuing to escalate with the increasingly elderly population. The global life expectancy is increasing steadily, and the number of elderly individuals is rising in every geographic region. Malaysia was projected to have three times the number of individuals aged 60 years and above in year 2020. Like most other Asian countries, Malaysia has a high prevalence of osteoporosis and its incidence will almost certainly increase together with Asia’s rapid growth in its aging population. Similar increment pattern was also reported in the incidence of related fragility fractures. Despite the significant developments in the pharmacotherapy of osteoporosis and post-menopausal complications, the risk of fragility fractures is by far not being eliminated and there are still unmet needs, requiring broader range preventive management steps. A systemic literature search was carried out with the use of specific keywords or phrases such as osteoporosis, fragility fracture, and/ or prevention of osteoporosis, particularly related to post-menopausal women (PMW) among Malaysians. Studies highlighted several common challenges in preventing osteoporosis and fragility fractures among PMW. These include early diagnosis (physical examination, screening and investigation) and prevention of osteoporosis, identification of risk factors of fragility fracture, limited education resources material that suite and tailor-made for Malaysian PMW, and limited utilisation of home-based care in the management and prevention of fracture among PMW. Poor knowledge among PMW on osteoporosis, prevention and risk prevention were also high. For example, it was not uncommon that PMW were unsure about the differences between osteoporosis and osteoarthritis. Some of the literature found that not only there was a lack of osteoporosis knowledge in patients but also among healthcare professionals. Additionally, PMW were found neglecting the consumptions of calcium in daily nutritional intakes. The majority only began incorporating milk (skimmed and full cream milk powder) into their diet within the past few years after they were informed of the impact of the diet on osteoporosis, while others reported that they never consumed milk. By understanding the needs of PMW based on specific population, a better interprofessional collaboration between healthcare professionals and non-governmental services can be structurally planned. It is imperative to develop effective educational program in order to make an impact on practice.